2010
DOI: 10.1007/s00464-010-1360-z
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal laparoscopically assisted endoscopic cholecystectomy: preliminary clinical results for a series of 43 cases in China

Abstract: Although endoscopic instruments specifically designed for NOTES are not available, the addition of an umbilical trocar is an optimal way to allow safe performance of NOTES procedures in an easily reproducible manner. The authors' initial experience demonstrates that this hybrid technique is potentially feasible and effective for reducing postoperative pain and recovery times while improving the cosmetic results of transvaginal cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 17 publications
3
36
0
1
Order By: Relevance
“…Many surgical interventions have been shown to be feasible using transvaginal access. Cholecystectomy and appendectomy are being performed in many centers [20,24,38]. Other, less frequently performed interventions include partial colectomy, nephrectomy, gastrectomy, hepatectomy, pancreatectomy, and gynecologic procedures [9,25,26,34,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Many surgical interventions have been shown to be feasible using transvaginal access. Cholecystectomy and appendectomy are being performed in many centers [20,24,38]. Other, less frequently performed interventions include partial colectomy, nephrectomy, gastrectomy, hepatectomy, pancreatectomy, and gynecologic procedures [9,25,26,34,39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have attempted to standardize patient selection criteria for THNC in order to achieve safe and effective clinical outcomes [4,14,18,36,37]. However, there is not an official consensus defining these criteria.…”
Section: Patient Selection (Preoperative Evaluation)mentioning
confidence: 99%
“…This concept was initially designed to access the abdominal cavity through different natural orifices such as the mouth, vagina, anus, and urethra [9,18,19]. In addition, several studies have shown applications in intrathoracic procedures including mediastinoscopy, thoracoscopy, and lymph node dissection [14,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…"Natural orifice specimen extraction" (NOSE) techniques that are similar to NOTES have been attempted in recent years. Transvaginal specimen extraction (TVSE), one of these techniques, has been attempted mainly in Europe and the USA, and it is claimed to have the advantages of reducing surgical wound pain, reducing wound complications, shortening the period of hospitalization, and ensuring excellent esthetic outcomes [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Widespread experience with laparoscopic pancreatectomies has allowed safe splenectomies in the supine position, by a safe and even less invasive surgical method using TVSE without the changing of body positions as required in conventional laparoscopic splenectomy [5][6][7][8][9][10]. The present surgical procedure was performed after obtaining approval from the Japanese Meabashi Red Cross hospital ethical committee.…”
Section: Introductionmentioning
confidence: 99%